UPAYA MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS BIOLOGI SISWA MELALUI MODEL PEMBELAJARAN KONTEKSTUAL (CONTEXTUAL TEACHING AND LEARNING) DENGAN BERBANTUAN MEDIA PPT DI SMA NEGERI 1 PANYABUNGAN UTARA - Ira Anugrah; Sahlan Tuah; Nurmaini Ginting (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
The problem in this research is the concept of critical biological thinking which became one of the most important things in the learning process that is through the application of Contextual Teaching Learning Model (CTL). The reason for this research is to know the improvement of critical thinking of student biology through the application of Contextual Learning Model an the material. The human Regulation system in class XI  IPA1 SMA Negeri 1 North Panyabungan academic year 2016-2017. This type of research is Classroom Action Research. Where the subject of study is the students of class XI IPA1 SMA Negeri 1 North Panyabungan consisting of 25 students. While techniques and data collected. Based on the result of critical thinking test of the biology of students cycle I am 76%, and cycle II is 84,33%, and the result of the increase of student activity in the cycle is I is 68% and cyle II 86,40%.Keywords: Critical thinking of student biology, Contextual Learning model (CTL), human regulatory system.